If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 42 + -2 = 2 + l Combine like terms: 42 + -2 = 40 40 = 2 + l Solving 40 = 2 + l Solving for variable 'l'. Move all terms containing l to the left, all other terms to the right. Add '-1l' to each side of the equation. 40 + -1l = 2 + l + -1l Combine like terms: l + -1l = 0 40 + -1l = 2 + 0 40 + -1l = 2 Add '-40' to each side of the equation. 40 + -40 + -1l = 2 + -40 Combine like terms: 40 + -40 = 0 0 + -1l = 2 + -40 -1l = 2 + -40 Combine like terms: 2 + -40 = -38 -1l = -38 Divide each side by '-1'. l = 38 Simplifying l = 38
| 7(8y+7)-6(8-7y)= | | y=x^2-15x+52 | | 2x^4+13x^3+12x^2-17x-10=0 | | 2(5-5r)+2(1-2r)=-4r-8r | | (2x+3*3)= | | 2x+6=24-8x | | 4(e+2)-6=-3(e-3) | | 1.5=.05x-1935 | | -0.35x=2.1 | | x+(2x+0.16)+(x+0.06)=1.4 | | 7=9+c | | (x+3)*2= | | 57-5x=31x+17 | | -s+7-(-1-3s)= | | lnx=-1.9 | | 9-9x=77-23x | | 1.5+98.35=.05x | | 0.3t-5=0.5t+1 | | y-6.5=8.2 | | x-7.8=6.53 | | y+5x+4x+5x=360 | | 16+3v=6v | | 0=-.004x^2+x+2.5 | | 2x^2+10x+7=0 | | 0.3t-5=0.5+1 | | 3ab-4b+5ab+4b= | | 10m=12 | | 4x^3+20x^2-68x-84=0 | | 15x-y+5(3x-2y+5z)= | | (2x+1)(x+4)=0 | | 10m-6=12 | | 6x^2-5s-6=0 |